Styk1 expression is a hallmark of murine NK cells and other NK1.1+ subsets but is dispensable for NK‐cell development and effector functions. Issue 5 (15th February 2019) - Fauteux, Sébastien; Faure, Fabrice; Marotel, Marie; Geary, Clair; Daussy, Cécile; Sun, Joseph C; Walzer, Thierry
Abstract: To gain insight into the biology of NK cells, others and we previously identified the NK‐cell signature, defined as the set of transcripts which expression is highly enriched in these cells compared to other immune subtypes. The transcript encoding the Serine/threonine/tyrosine kinase 1 (Styk1) is part of this signature. However, the role of Styk1 in the immune system is unknown. Here, we report the generation of a novel transgenic mouse model, in which Styk1 expression is invalidated and replaced by an EGFP reporter cassette. We demonstrated that Styk1 expression is a hallmark of NK cells and other NK1.1 expressing cells such as liver type 1 innate lymphoid cells (ILC1) and NK1.1 + γδ T cells. Styk1 expression is maintained by IL‐15 in NK cells and negatively correlates with the expression of educating NK‐cell receptors. Analysis of phosphorylation levels of mTOR substrates suggested that Styk1 could moderately contribute to the activity of the PI3K/Akt/mTOR pathway. However, Styk1‐deficient NK cells develop normally and have normal in vitro and in vivo effector functions. Thus Styk1 expression is a hallmark of NK cells, ILC1 and NK1.1 + T cells but is dispensable for their development and immune functions. Abstract : Styk1 is specifically expressed by NK cells and at a lower level by other NK1.1 + cells such as ILC1 and gd T cells. Styk1 expression is not essential for NK cell effector functions.